The Analysis Effect of Leverage, Asymmetric Information and Corporate Governance to Firm Value in Manufacture Companies Listed in Indonesia Stock Exchange - Octaviana, Lisa Tyas; Hasnawati, Sri; Hendrawaty, Ernie (International Journal of Economics, Business, and Entrepreneurship, 2019)
Company value or Firm value is a certain condition that has been achieved by the company as an illustration of public trust and shareholders towards the company after going through an activity process for several years, since the company was first established until now. This study aims to determine the effect that occurs between Leverage, Asymmetric Information, and Corporate Governance on the Firm Value through Cash Holdings as a mediating variable. The data used in this study are published financial report from 33 manufacturing companies in the Consumer Goods Industry Sector listed on the Indonesia Stock Exchange from 2011 - 2017. The conclusion of this study is that cash holdings are only able to mediate the influence of corporate governance with a proxy proportion of the board independence on firm value. Directly cash holding and corporate governance with a proxy proportion of the number of independent commissionersalso influence the firm value while leverage, asymmetric information and corporate governance with a proxy percentage of the number of share ownership by managerial do not directly affect the firm value of the company. So as to increase the value of the company, companies should determine the proportion of the right amount of board independence so it can create good corporate governance that can increase value of the company.